Impact of climate on photovoltaic battery energy storage system optimization. (May 2022) - Liu, Jiangyang; Liu, Zhongbing; Wu, Yaling; Chen, Xi; Xiao, Hui; Zhang, Ling
Abstract: The optimization of the battery energy storage (BES) system is critical to building photovoltaic (PV) systems. However, there is limited research on the impact of climatic conditions on the economic benefits and energy flexibility of building PV–BES systems. Taking an office building as an example, a method for minimizing the total cost of a PV–BES system was established using a mixed integer nonlinear programming model to optimize the BES capacity. Then, the effects of the grid import/export power limit and peak feed-in tariff on BES capacity optimization were investigated, and the various economic benefits of the PV–BES system were discussed and analyzed accordingly. The results show that the operating cost was reduced significantly when the PV–BES system was employed in any of the evaluated climates; the relative payback period of the PV–BES system in Changsha was the minimum at 1.4 years. The grid import power limit and the peak feed-in tariff had a much greater impact on the battery capacity, energy flexibility, and economic benefits of the PV–BES system than the grid export power limit. The results of this study provide guidance for the application of PV–BES systems in different climates.